ChemInform Abstract: A Green and Expedient Synthesis of Enantiopure Diketopiperazines via Enzymatic Resolution of Unnatural Amino Acids. Issue 8 (February 2015) - Pereira, Pedro C.; Arends, Isabel W. C. E.; Sheldon, Roger A.
Abstract Dipeptides (III) are stereoselectively prepared from D‐phenylglycine amide and racemic amino acids in the presence of an immobilized form of penicillin G acylase in aqueous medium.